Mirages in the desert: the tradition-historical developments of the story of Massah-Meribah - Garton, Roy E. ca. 20./21. Jahrhundert (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2017)
The story of Massah-Meribah is a pluriform tradition within the Hebrew Bible. Part One of this book uses redaction analysis to assess diachronically the six reminiscences of this tradition within Deuteronomy (Deut 6:16; 8:15; 9:22; 32:13, 52; 33:8). The relative chronological relationship of these texts, and the tradition components they preserve, reveals a framework of five formative stages of this story's tradition-history from the perspective of the tradents responsible for the production of Deuteronomy. Part Two is a redactional study of the tradition's narratives in Exod 17:1-7 and Num 20:1-13. Special attention is devoted to the texts that anchor the Massah-Meribah narratives into the Pentateuch. In the end, Part Two not only corroborates the framework detected in Deuteronomy for the formative stages of the Massah-Meribah tradition, but it also carries broad implications for the formation of the Pentateuch in general and the Wilderness Narrative in particular.